2015
DOI: 10.1038/ncomms7041
|View full text |Cite
|
Sign up to set email alerts
|

The phase diagram of electron-doped La2−xCexCuO4−δ

Abstract: Superconductivity is a striking example of a quantum phenomenon in which electrons move coherently over macroscopic distances without scattering. The high-temperature superconducting oxides (cuprates) are the most studied class of superconductors, composed of two-dimensional CuO 2 planes separated by other layers that control the electron concentration in the planes. A key unresolved issue in cuprates is the relationship between superconductivity and magnetism. Here we report a sharp phase boundary of static t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 31 publications
7
42
0
Order By: Relevance
“…The T c was typically 20 ± 1 K. As typical, the normal-state resistivity (in a field above H c2 ) shows a low-temperature upturn. These LCCO films are similar to those prepared for other experiments by the Maryland group ( 44 ). Further details can be found in the Supplementary Materials.…”
Section: Methodssupporting
confidence: 82%
“…The T c was typically 20 ± 1 K. As typical, the normal-state resistivity (in a field above H c2 ) shows a low-temperature upturn. These LCCO films are similar to those prepared for other experiments by the Maryland group ( 44 ). Further details can be found in the Supplementary Materials.…”
Section: Methodssupporting
confidence: 82%
“…However, recent experimental studies have shown that, in the electron-doped systems, the electron correlation strength is not so strong that even very lightly doped samples exhibit superconductivity if they are properly annealed and the antiferromagnetism is suppressed. Some of these studies suggest that superconductivity persists even with no electron doping, [1][2][3] while others show presence of antiferromagnetic long range order in the lightly doped regime, 4,5) so that the issue is still controversial. It was also shown experimentally that the "pseudo gap", [6][7][8][9][10] a prominent feature of the cuprates, disappears if the antiferromagnetism is suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…Photoemission (ARPES) experiments are consistent with a large FS in overdoped n-doped materials [10][11][12], and show evidence for both electron-and hole-like pockets as x decreases below ∼ 0.16. However, many issues remain unresolved, including the structure of the FS and nature of its reconstruction and evolution with doping, reconciling quantum oscillation measurements with the observation of Fermi arcs [13,14] in the pseudogap phase, and identifying the true nature of the competing ground state (whether arising from observed magnetic [15,16] …”
mentioning
confidence: 99%
“…Photoemission (ARPES) experiments are consistent with a large FS in overdoped n-doped materials [10][11][12], and show evidence for both electron-and hole-like pockets as x decreases below ∼ 0.16. However, many issues remain unresolved, including the structure of the FS and nature of its reconstruction and evolution with doping, reconciling quantum oscillation measurements with the observation of Fermi arcs [13,14] in the pseudogap phase, and identifying the true nature of the competing ground state (whether arising from observed magnetic [15,16] charge [17], or predicted d-density wave (DDW) [18]) order). QO have only been observed in a restricted doping range (x = 0.15 -0.17) in n-doped bulk crystals of Nd 2−x Ce x CuO 4 (NCCO) [19][20][21], and found to be consistent with a theoretical picture of DDW-like order [22,23].…”
mentioning
confidence: 99%